Cross Cultural Leadership and Team Effectiveness in Global Virtual and Hybrid Teams: A Systematic Literature Review - Dedi Supiyadi; Syamsul Hadi Senen; Rofi Rofaida (Indonesian Scientific Publication, 2026)
The global shift toward virtual and hybrid work has intensified the complexity of cross-cultural leadership, particularly in relation to coordination, communication, and relational processes in digitally mediated environments. Although research on global leadership, cultural intelligence, and virtual teams has grown substantially, understanding of how cross-cultural leadership behaviours influence team effectiveness through psychosocial mechanisms under varying cultural conditions remains fragmented. To address this gap, this study conducts a systematic literature review of 50 peer-reviewed journal articles published between 2010 and 2025 and indexed in Scopus. The synthesis reveals a recurring pattern indicating that adaptive cross-cultural leadership behaviours are associated with the effectiveness of global virtual and hybrid teams through relational and communicative mechanisms, most notably trust, communication quality, and psychological safety. Cultural factors, including national value differences, power distance, and multicultural diversity, emerge as important moderators shaping how leadership behaviours are interpreted and enacted within distributed teams. The findings further suggest that the degree of virtuality and the characteristics of communication media condition the strength and nature of these relationships. The primary contribution of this review lies in the development of an integrative conceptual model that links cross-cultural leadership behaviours, psychosocial mechanisms, and team effectiveness in virtual and hybrid contexts. By doing so, this study extends theoretical insights from global leadership and cultural intelligence research into digitally mediated work settings and provides a structured foundation for future research and global human resource management practice.